Modiano and Sebald: Walking in Another's Footsteps - Steven Ungar (Studies in 20th & 21st Century Literature, 2007)
This article studies Patrick Modiano's Dora Bruder (1997) and W.G. Sebald's Austerlitz (2000) in conjunction with a contemporary literature of diaspora grounded in the extended aftermath of World War II. Both texts straddle fiction and testimonial accounts such as memoirs, letters, and video/audio recordings. In addition, both raise questions with which traditional historians seldom contend, even when they group these questions under the category of memory. What understanding of the recent past might these two narratives promote? What do they imply—individually or as a set—concerning the nature and function of the historical subjectivity that literature can convey? Each in its own way, Dora Bruder and Austerlitz override conventions of literary genre by mixing elements of novel, autobiography, and essay. Accordingly, language becomes a prime point of inquiry in conjunction with the double question most likely to be raised in terms of the historical record: who is writing and to what end or purpose? These questions, in turn, direct inquiry to enunciation and point of view as components of historical subjectivity associated with the literature of a post-World War II diaspora.
Keywords: Patrick Modiano; Dora Bruder; W.G. Sebald; Austerlitz; literature of diaspora; World War II; memoirs; letters; video/audio recordings; memory; novel; autobiography; essay; post-World War II